Countering prejudice and discrimination: Women musicians in the pursuit of socio-economic advancement and social affirmation in interwar Yugoslavia - Vesić Ivana (Muzikologija, 2025)
This paper explores the challenges and efforts of women musicians in interwar Yugoslavia to improve their working conditions and oppose widespread prejudices. Despite relatively favorable conditions in the Yugoslav labor market for professional musicians, women musicians faced numerous obstacles due to prevalent patriarchal norms and negative representations. These issues were exacerbated by state regulations and policies, as well as the hostile approach of male musicians and biased media framing. I will discuss in detail the dominant narratives on women musicians and the attempts at creating a professional labor organization. The aim is to emphasize the intricate array of factors that shaped working conditions and everyday life of women musicians in interwar Yugoslavia, as well as the endeavors of this group to enhance their socio-economic standing and make their voices heard in the public sphere.